Analysis of the theoretical framework of the REA accounting model Used in the design of accounting information systems - عبد الله سلمان حسين (Journal of Economics and Administrative Sciences, 2009)
Researchers often equate database accounting models in general and the Resources-Events-Agents (REA) accounting model in particular with events accounting as proposed by Sorter (1969). In fact, REA accounting, database accounting, and events accounting are very different. Because REA accounting has become a popular topic in AIS research, it is important to agree on exactly what is meant by certain ideas, both in concept and in historical origin. This article clarifies the analyzing framework of REA accounting model and highlights the differences between the terms events accounting, database accounting, semantically-modeled accounting, and REA accounting. It also discusses potentially productive directions for AIS research.